The revolution which toppled the Umayyads : neither Arab nor ʻAbbāsid - Āghā, Ṣāliḥ Saʻīd (Islamic history and civilization, 2003)
This work re-examines the so-called Abbasid revolution, the ethnic character of whose effective constituency has been contested for over eight decades. It also brings to question the authenticity of the Abbasid dynastic claim.